TINJAUAN YURIDIS PENYELESAIAN KREDIT BERMASALAH (MACET) OLEH PANITIA URUSAN PIUTANG NEGARA - Iswandi Palangit (LEGAL OPINION, 2025)
The author's conclusion is: From the description above, the author can conclude that as a mandate of Law Number 49 Prp of 1960 PUPN is given full authority to manage state receivables which are operationally carried out by KP2LN which carries out administrative activities for managing state receivables as well as implementing all decisions issued by PUPN such as making joint statements (PB), notices, forced letters, confiscation implementation, to the auction process. In its operations PUPN / KP2LN often also encounters obstacles both internally and ex-ternally but still strives for the best solution in its resolution. PUPN / KP2LN often encounters obstacles in terms of vacating the auction ob-ject because it still involves other agencies, namely the auction winner must submit a request to vacate the object purchased through auction to the local District Court if the occupants are not willing to leave volun-tarily. Kesimpulan penulis yaitu: Dari uraian diatas dapat penulis simpulkan sebagai mandate undang-undang Nomor 49 Prp tahun 1960 PUPN diberikan kewenangan penuh untuk mengurus piutang negara yang secara operasional dilaksanakan oleh KP2LN yang melaksanakan kegiatan administrasi kepengurusan piutang Negara sekaligus melaksanakan semua keputusan yang dikeluarkan oleh PUPN seperti pembuatan pernyataan Bersama (PB), Pemberitahuan, Surat Paksa, Pelaksanaan Penyitaan, sampai proses lelang. Didalam operasionalnya PUPN/KP2LN sering pula menemui kendala-kendala baik internal mau-pun external namun tetap diupayakan solusi yang terbaik didalam penyelesaiannya. PUPN/KP2LN sering menemui hambatan dalam hal pengosongan objek lelang karena masih melibatkan instansi lain yaitu pemenang lelang harus mengajukan permohonan pengosongan terhadap objek yang dibeli melalui lelang kepada Pengadilan.